Direct Cervicoplasty - Jordan, J. Randall (Facial Plastic Surgery, 2012)
The sagging neck, or “turkey gobbler” deformity, is one of the more common reasons that patients present to facial plastic surgeons. Although many of these patients might be best improved by a full rhytidectomy with periauricular incisions, skin flap undermining, and platysmal tightening, there are some patients who do not wish to undergo a full rhytidectomy. Some of these patients may be reasonably well served by a direct cervicoplasty or submentoplasty. The advantages of this approach include shorter operative time, faster recovery, and lower complication rates. The primary disadvantage is an anterior cervical incision that may be visible under some conditions. This article will review the options for skin incisions as well as technical details that may lead to a successful rejuvenation of the submental region.
Keywords: cervicoplasty; submentoplasty; rhytidectomy; platysmaplasty